THE EFFECT OF PHYSICAL REHABILITATION ON THE SPEED AND COMPLETENESS OF RECOVERY AFTER SERIOUS INJURIES AND/OR SURGICAL INTERVENTION - Bilyk, L. V.; Hnatyuk, V. V.; Rastorguyeva, I. S. (Rehabilitation and Recreation, 2023)
Purpose. The purpose of the study is to identify the impact of physical rehabilitation on the speed and completeness of recovery after severe injuries and/or surgical intervention. Material. The participants of the study are the first group – 10 respondents (5 women and 5 men) aged 25–37, who are undergoing rehabilitation after severe injuries of the musculoskeletal system. Their physical rehabilitation is unpredictable; the second group – 10 respondents (7 men and 3 women) aged 24–39, who are undergoing rehabilitation after severe musculoskeletal injuries. Physical rehabilitation is provided for them; the third group – 10 respondents (10 women) aged 21–41, who are undergoing rehabilitation after surgical intervention to remove benign breast tumors. Their physical rehabilitation is unpredictable; the fourth group – 10 respondents (9 women and 1 man) aged 23–36 years who are undergoing rehabilitation after surgical intervention to remove benign breast tumors. Physical rehabilitation is provided for them. The study took place in the period from March 1, 2023 to September 11, 2023. The research of groups 1 and 2 was carried out on the basis of the International Center of Neurosurgery (Kyiv) and groups 3 and 4 on the basis of the National Cancer Institute (Kyiv). The research was conducted in the form of a survey and study of medical records. The results. The conducted study revealed that patients from the 2nd group who underwent physical rehabilitation fully recovered 1 month faster than patients from the 1st group; patients from the 4th group fully recovered 1.5 months faster than patients from the 3rd group. That is, physical rehabilitation has a positive effect on the recovery process of patients, especially if patients have undergone surgical intervention. At the same time, such physical rehabilitation involves various forms and types of exercises. Conclusions. It is advisable to use physical rehabilitation during the treatment of patients who have suffered a severe injury or had surgery. At the same time, it must be combined with psychological work with the patient.